(untitled) (Rehabilitation and Recreation, 2024)
The article presents the results of research on changes in the field of vision of schoolchildren during the use of ringo game tools. The purpose of the study is to determine the dynamics of the peripheral field of vision of sixth-graders in physical education lessons while learning the game of ringo. Research methods: theoretical analysis of scientific and methodical literature, testing of peripheral vision using Forester’s perimeter, pedagogical experiment, methods of mathematical statistics. 55 students of the 6th grade took part in the study: 27 students (12 ♂, 15 ♀) were the experimental group, 28 (14 ♂ and 14 ♀) were the control group. In the lessons of physical education in the experimental group, learning to play ringo was introduced as a variable component. Before the experiment, it was found that the groups were homogeneous, there were no statistically significant differences in visual field indicators between schoolchildren of the control and experimental groups (P>0.05) At the end of the pedagogical experiment after learning to play ringo, the experimental group of sixthgrade children improved their peripheral vision. The obtained indicators of the peripheral field of vision, color and silhouette sensitivity of the eye prove the effectiveness of using the ringo game in physical culture lessons with sixth-grade students. As a result of the study, it was established that the introduction of the ringo game into the educational process, as a variable module in physical education lessons, has a positive effect on the development of indicators of the peripheral field of vision of sixth graders. Comparing the results of the field of vision of the students of the experimental group obtained at the beginning and at the end of the study, an improvement in the silhouette sensitivity of the right eye at the perimeter arc angles of 0° (p<0.001) and 225° (p<0.05), and the color sensitivity of the right eye was found at angles of 0° (p<0.001) and 225° (p<0.001), as well as silhouette sensitivity of the left eye at an angle of 270° (p<0.05). A comparison of the results of visual field indicators in CG students at the beginning and at the end of the experiment did not reveal any positive changes (p>0.05). At the end of the experiment, EG schoolchildren outperformed their peers from CG in terms of silhouette and color sensitivity of the right eye at perimeter arc angles of 0°, 45°, 225° (p<0.001). In terms of silhouette and color sensitivity of the left eye, the advantage of EG schoolchildren was observed at the angles of the perimeter arc of 0° and 135° (p<0.001) and for the silhouette – 225° and 270° (p<0.05). In all other cases, differences in the parameters of the field of silhouette and color sensitivity of the eyes were observed, but they were not significant (p>0.05).